Engineering of optogenetic devices for biomedical applications in mammalian synthetic biology. Issue 2 (7th July 2022) - Guan, Ningzi; Gao, Xianyun; Ye, Haifeng
Abstract: Gene‐ and cell‐based therapies are the next frontiers in the field of medicine. Both are transformative and innovative therapies; however, a lack of safety data limits the translation of such promising technologies to the clinic. Improving the safety and promoting the clinical translation of these therapies can be achieved by tightly regulating the release and delivery of therapeutic outputs. In recent years, the rapid development of optogenetic technology has provided opportunities to develop precision‐controlled gene‐ and cell‐based therapies, in which light is introduced to precisely and spatiotemporally manipulate the behaviour of genes and cells. This review focuses on the development of optogenetic tools and their applications in biomedicine, including photoactivated genome engineering and phototherapy for diabetes and tumours. The prospects and challenges of optogenetic tools for future clinical applications are also discussed.